1982
DOI: 10.1007/bf02391940
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in whole lake sediments — towards a loading estimate

Abstract: Studies of nutrient loadings, to shallow culturally eutrophied Alberta lakes, suggest internal inputs are significant. In this regard, estimation of bottom sediment P loads to Lake Wabamun (80 km 2 , 5.5 m x depth) were examined. Initially we determined the spatial variability in Total Organic Content (% loss on ignition) and Total Phosphorus, as indicators. Phosphorus fractions and biologically available phosphorus (BAP) were measured at specific stations. These data showed a very uniform distribution in sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This finding is in basic agreement with Reynoldson and Hamilton (1982). Most other sediment characteristics require greater sampling effort near the minimum concentrations that we encountered: 300 samples for pigments, 80 samples for organic matter (dry mass), 20 samples for water content.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This finding is in basic agreement with Reynoldson and Hamilton (1982). Most other sediment characteristics require greater sampling effort near the minimum concentrations that we encountered: 300 samples for pigments, 80 samples for organic matter (dry mass), 20 samples for water content.…”
supporting
confidence: 90%
“…Twinch and Peters 1984) or station (e.g. Reynoldson and Hamilton 1982). Although some researchers have shown high coefficients of variation, C.V. = 100 (s2/mean), among replicate cores taken at the same site (Hargrave and Nielsen 1977;Slater and Boag 1978;Anderson et al 1982), it is unclear whether this "heterogeneity" results from spatial variation or analytical error (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increased phosphorus loading of the experimental period was 'diluted' and thus little was returned even under anaerobic conditions. Shallow eutrophic lakes in Alberta showed mixing to a depth of 16 cm (Reynoldson and Hamilton, 1982) which regulated phopshorus release .. Lakes which have been eutrophic for longer periods would, on this explanation, be expected to show progressively greater phosphorus return from internal loading because their sediments are saturated.…”
Section: Changes In the Cycles Which Occur As A Consequence Of Enhancmentioning
confidence: 92%
“…Some mechanisms affecting sedimentary processes have also been distinguished, such as turbidity currents from delta foreslopes that affect deep water depositional pattern (Lamoureux, 1999). Reynoldson and Hamilton (1982) suggested that wind action could disturb bottom sediment, resulting in homogeneous sediments, whereas other studies suggested wind was a forcing factor for uneven sediment distribution patterns (Odgaard, 1993;Whitemore et al, 1996). Bacterial oxidation (Hilton and Gibbs, 1984), benthic animals' activity (Downing and Rath, 1988), industrial distribution and land use conditions Rose et al, 1998;Gälman et al, 2006) are all influencing factors that can affect the distribution of sediments.…”
Section: Introductionmentioning
confidence: 95%